PROGESTERONE PROFILES AND CHANGE IN RECTAL TEMPERATURE IN INDUCED WHELPING BITCHES - REDDY, K.RAM CHANDRA; RAO, K SADASIVA; RAJU, K G S; REDDY, A G (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted in 29 clinical cases. Whelping was induced by using cloprostenol, dinoprostone plus cloprostenol and mifepristone plus cloprostenol. The mean duration of time interval from starting of treatment to beginning of whelping was 34.46 ± 4.70, 40.48 ± 6.47and 26.98 ± 4.51 hours in three treatment groups respectively. The mean plasma progesterone concentrations were 3.89 ± 0.54, 3.54 ± 0.31, 2.72 ± 0.41 and 3.83 ± 0.2 ng/ml before starting of treatment; 1.92 ± 0.13, 1.86 ± 0.12, 2.87 ± 0.5 and 1.55 ± 0.21 ng/ml at 2 to 12 hours before whelping and 0.56 ± 0.06, 0.53 ± 0.08, 1.18 ± 0.4 and 0. 7 4 ± 0.13 ng/ml during O to 6 hours after whelping in three treatment groups respectively. The mean rectal temperature was 101.23 ± 0.20, 101.62 ± 0.17, 101.86 ± 0.30 and 102.08 ± 0.08 °F before starting of treatment; 99.98 ± 0.53, 100.85 ± 0.28, 101.43 ± 0.35 and 100.5 ± 0.22 °F at 12 hours after treatment; 99.94 ± 0.21, 100.15 ±0.3, 101.5 ± 0.38 and 99.95 ± 0.24 °Fat 24 hours after treatment; 100.75 ± 0.48, 101.79 ± 0.10, 101.88 ± 0.32 and 101.3 ± 0.14 °Fat 36 hours after treatment and 101.5 ± 0.75, 102.0 ± 0.5 and 101.8 ± 0.16 °Fat 48 hours after treatment in cloprostenol, dinoprostone plus cloprostenol, mifepristone plus cloprostenol and control groups respectively.